Ethanol Purification Using Activated Natural Zeolite - Purnomo, Chandra Wahyu; Putri, Nelliza; Perdana, Indra; Hinode, Hirofumi (Makara Journal of Technology, 2017)
Bio ethanol is one of the potential fuels in the future. However, ethanol in water mixture has an azeotropic concentration of 95.6 wt. %, which makes it difficult to purify further. The common method of purification is by using an azeotropic distillation column, which requires an intensive energy and an addition of specific solvent. In this study, ethanol purification is done using an adsorption column packed with zeolite Raschig rings. The natural zeolite ring was modified beforehand using the NaOH solution to enhance the material’s water adsorption performance. The ethanol purity can reach more than 99% with the modified zeolite packing. The modification also increases the saturation time of the packed bed column, thus making it more efficient.